Metode dan Model Pengembangan Gereja Berbasis Layanan Digital - Silaban, Ferdesly; Marbun, Purim (Sekolah Tinggi Teologi Injili Indonesia Palu, 2025)
The advancement of the modern era has significantly influenced human lifestyles and habits. Technological progress has transformed how people communicate, work, and access information, including a major shift from traditional print media to digital formats for reading and learning. This societal change extends to the realm of church ministry, which now faces the need to adapt in order to remain relevant and effective. Churches are called to respond to this shift by integrating digital services as part of their mission to fulfill Christ’s mandate. This study reveals that developing the church through digital platforms is not merely an option but a necessity in the contemporary world. Digital-based church ministry has shown substantial benefits in expanding outreach, enhancing congregational engagement, and supporting spiritual growth more effectively. A church that embraces digital service can become a powerful means to realize the mission of Christ in a rapidly changing world